TECHNICAL AND TECHNOLOGICAL RE-EQUIPMENT INDUSTRY OF LIVESTOCK - Лаврук, В. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The article deals with the problem of economic modernization necessity; technical and technological reequipment of the livestock industry contributing to its development sustainability and livestock production increase; required to meet the needs of population in nutritional food and country’s food security provision. These issues have important values and; therefore; require a comprehensive study; based on application of economic and statistical analysis methods and selective sociological survey; allowing to identify; systematize and justify the most important factors that directly influence the increase of production volumes and the animal products major types quality. The aim of the research is the process of technical and technological modernization of the livestock industry in the context of enhancing the competitiveness and efficiency of livestock production. It was established that the technical and technological re-equipment of livestock implies the introduction of modern vehicles; machinery and equipment of domestic and foreign designs; new technologies of production; organizational and managerial practices contributing to the enhancement of the livestock enterprises production economic activities efficiency. It was proved that in future the effective modernization of livestock should become a prerequisite of its innovative development. Major directions and ways of livestock technical and technological re-equipment improvement and livestock enterprises efficient development were defined.